Productivity‐Enhancing Labour Reallocation in Australia†. Issue 317 (31st March 2021) - Andrews, Dan; Hansell, David
Abstract : Using firm‐level data, we examine the efficiency of labour reallocation in Australia over the period 2002–16. We find that more productive firms account for a higher share of employment – particularly in trade‐exposed sectors – and Australia appears more successful at reallocating resources to high‐productivity firms than many OECD countries. But the propensity for high‐productivity firms to expand and low‐productivity firms to contract (or exit) has declined over time. Counterfactual estimates suggest this decline in productivity‐enhancing labour reallocation is a key feature of Australia's productivity slowdown.